A novel validated simple derivatization liquid chromatographic method with diode array detection for the simultaneous determination of mancozeb, azoxystrobin and difenoconazole in pesticide dosage form. Issue 9 (15th February 2022) - Patil, Vilas K.; Wagh, Ujwala B.; Phalak, Raju P.; Bhirud, Jayashri D.; Narkhede, Hemant P.
Abstract : A novel, rapid and simple reverse-phase high performance liquid chromatography (RP-HPLC) method for the simultaneous determination of three pesticides – mancozeb, azoxystrobin and difenoconazole by derivatization with ethyl iodide is presented. Abstract : A novel, rapid and simple reverse-phase high performance liquid chromatography (RP-HPLC) method for the simultaneous determination of three pesticides – mancozeb, azoxystrobin and difenoconazole by derivatization with ethyl iodide is presented. Analysis was performed on a C18 column (Agilent Eclipse plus, 150 mm × 4.6 mm; 5 μ) with the mobile phase consisting of acetonitrile + methanol (90 + 10 v/v) – water (0.1% v/v trifluoroacetic acid) (60 : 40, v/v) pumped isocratically at a flow rate of 1.0 mL min −1 and detection wavelength of 205 nm and 272 nm. The factors affecting the derivatization reaction and separation conditions were carefully evaluated and optimized. The method was linear over the concentration range of 3.50 mg L −1 to 31.48 mg L −1 for mancozeb, 0.32 mg L −1 to 2.85 mg L −1 for azoxystrobin and 0.32 mg L −1 to 2.89 mg L −1 for difenoconazole. The new method was successfully applied for the analysis of mancozeb, azoxystrobin and difenoconazole in the pesticide formulation with range recoveries of 99.46% to 100.76%, 99.07% to 101.09% and 98.59% to 101.59%, respectively. The present method is suitable and favorable for the simultaneous separation and analysis of tertiary mixture analytes on account of its sensitivity, rapidity and cost-effectiveness. In addition, it could have excellent application prospects for the simultaneous determination of all three pesticides in other formulated products.